Utilizing Simple Practicals to Understand the Process of Changes in the State of Matter in the Context of Everyday Life - Ninda Audiska; Icha Fadillah Putri; Tria Desfika; Nurul Hasanah (JURNAL ILMIAH NUSANTARA, 2025)
Practical activities are a fun and effective way to help students understand concepts in science lessons, especially the material on changes in state of matter. This study aims to see how simple practicals can be used as a concrete learning tool in understanding various processes of changes in state of matter such as melting, freezing, sublimation, evaporation, condensation, and crystallization. The practicals were carried out by PGSD students using tools and materials that are easily found in everyday life, such as ice cubes, water, candles, camphor, and small containers. During the activity, students made direct observations of changes in state of matter and recorded the time of the changes systematically. The results of the practicals showed that students found it easier to understand the process of changes in matter when they were directly involved in the experimental activities. The learning process becomes more enjoyable, not only through theory, but also through real-life experiences that they can see and feel for themselves. Students also become more active in discussions, work collaboratively in groups, and are able to relate their observations to events they frequently encounter in their daily lives. Thus, this simple lab exercise is not only beneficial for strengthening understanding of scientific concepts but also fosters curiosity, logical thinking skills, and a scientific attitude in students. This type of lab exercise is highly recommended for science learning because it has been proven to make the learning process more lively, enjoyable, and meaningful.